GENDER DAN PEMBANGUNAN PEREMPUAN DI ACEH PASCA KONFLIK DAN TSUNAMI: PEMBAHASAN TEORITIS - Yeni Sri Lestari (Jurnal Community, 2017)
This article discusses the theoretical analysis of gender and its relationship to women's development in post-conflict Aceh and the tsunami. This discussion is considered important because of two causes, first the development of women in most countries is always focused on the gender concepts that discuss the position of men and women from the socio-cultural side that influence development in particular in this study is the development of women's rights Aceh . While the development of women is still minimal has led to demands for the fulfillment of women's rights in Aceh. Based on this, then the issues studied in the discussion of this article are  what is meant by gender and how can gender be formed? What is the relationship between gender concepts and women's development process in Aceh ?. The findings of the study found that the concept of gender is an important contributor to the birth of women's power in advocating for the development of their rights in post-conflict Aceh and the tsunami. This is because the concept of gender provides a great opportunity for the existing women's movements in various parts of the world, especially in post-conflict Aceh and tsunami in Aceh. At the end of the study, this article shows that gender plays an important role in the development of women's rights in Aceh.Keywords: Gender, Development of women, Aceh, Conflict and Tsunami.